ANALISIS SEKTOR UNGGULAN AGRIBISNIS PRIMER DI PROVINSI JAWA BARAT - Nana Danapriatna; M. IKhwan Rahmanto (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2006)
This research aim to know map of eminent sector of primary agribusiness in Province West. Result of this research indicate that eminent sector of primary agribusiness in Province West Java there are 11 sub-province/town, that is Sub-Province of Garut, Cianjur, Kuningan, Tasikmalaya, Sukabumi, Cirebon, Ciamis, Majalengka, Sumedang, Subang, and Town of Banjar